Research on Communication Simulation of PROFIBUS Multi-master System - Sun, Hongxiao; Zhe, Qiang; Rao, Ziyi; Liu, Yuliang; Liang, Geng (International Journal of Mechanical and Electrical Engineering, 2024)
As the application background of fieldbus becomes more and more extensive, PROF I BUS contains multiple master stations, and a multi-master system with multiple slave stations emerges at the historic moment. This paper establishes a multi-master communication system model and uses simulation technology to study the relationship between the target token cycle time, token waiting time, and master site address value.